Double Threaded Screw Fixation for Bilateral Stress Fracture of the Medial Malleolus - Ryo Kanto; Shigeo Fukunishi; Takatoshi Morooka; Daisuke Seino; Takayuki Takashima; Shinichi Yoshiya; Juichi Tanaka (Case Reports in Orthopedics)
An 18-year-old college basketball player presented with continued ankle pain. A radiographic examination showed bilateral medial malleolus stress fractures. Considering the prolonged history and refractory nature of this injury, surgery was adopted as a treatment option. At surgery, the fracture site was percutaneously fixed using two cannulated double threaded screws. Surgery for each side was sequentially performed two months apart. Prompt bony healing was attained after surgery, and the patient could return to his previous sports level six months after the first surgery without subsequent recurrence.